An Investigation of How Open Selection System Will Be Implemented In 2021 For Primary High Leadership Positions In The Government of Gayo Lues Regency - Afni*, Hardi; Nurhafni, Nurhafni; Muhtarom, Muhtarom (Riwayat: Educational Journal of History and Humanities, 2024)
Filling High Leadership Positions within Government Agencies is a guideline for central and regional government agencies in carrying out the filling of major, middle and primary high leadership positions in an open and competitive manner. The aim of the research is to find out how to implement, supporting factors, inhibiting factors and efforts in implementing open selection for first high leadership positions. The theory used is the theory of public policy implementation. The research method uses qualitative research methods. The implementation of the open selection policy for senior high leadership positions within the Gayo Lues Regency Government has been running in accordance with Law Number 5 of 2014 concerning State Civil Apparatus. However, the implementation of this policy is not optimal because there are still inhibiting factors in implementing the policy. Efforts that can be made by implementers to maximize the implementation of the JPT first open selection in Gayo Lues Regency include increasing the budget, facilities and infrastructure, re-evaluating the parties involved. Future research can look at it from the perspective of rationalization in the education level for participating participants. take part in the JPT first open selection